The Assessment of Sanatorium Treatment Impact on the Results Obtained in the Oswestry Questionnaire in the Areas of Sitting, Standing and Sleeping - Anna Antczak-Komoterska; Karolina Filipska; Beata Haor; Robert Ślusarz (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Back pain in the lumbar spine has become the most common disorder of the 21st century. Nearly 80% of population aged over 40 have already experienced a painful episode in their spine. Aim. The aim of the study is to assess to what extent the rehabilitation influences the occurrence of pain while sitting, standing and sleeping in patients with lumbar spine pain syndromes. Material and Methods. The research was conducted among 300 (100%) respondents aged 35–65. The studied population included 111 women, i.e. 37% and 189 men — 63%. Most people declared secondary education (40%), which was followed by vocational education (29%) and then higher education (24%). Patients were treated for lumbar spine pain syndromes. The research was carried out at the Sanatorium “Uzdrowisko Wieniec” Sp. z o.o. in Wieniec Zdrój. Results. After the end of the stay, it was noticed that the number of people who could sit in the chair any number of hours significantly increased (p≤0.05) from 7% to 29%, while the number of respondents who could stand any number of hours also increased (p≤0.05) from 4% to 26%. On the day of discharge from the sanatorium, the number of people declaring that pain does not affect sleep also significantly increased (p≤0.05) from 96 out of 167 of those surveyed. Conclusions. Taking into account the intensity of pain, it can be concluded that after the sanatorium treatment the number of responses related to the reduction of pain symptoms increased. Significantly increased the number of those who can sit, stand and sleep without pain in the lumbar region. (JNNN 2018;7(2):70–74)